Characterization Of Yogurt With The Addition Of Vegetables To Increase Antioxidants - Syaubari Syaubari; Nasrullah Razali; Muhammad Fannka Dhedia; Kevin Sadelah (Journal of Applied Technology, 2022)
Antioxidant activity can neutralize free radicals in the body and prevent chronic degenerative diseases. Therefore yogurt has a higher antioxidant potential than milk because lactic acid bacteria in yogurt produce antioxidant peptides. To increase antioxidant activity in yogurt, vegetable extracts such as Broccoli and carrots are added as food sources that are high in antioxidant activity. The experiment was carried out by an experimental method with the addition of 20% vegetable extract, 5% skim milk and 3% and 5% yogurt starter by using variations of UHT Cow milk and 600 ml Goat Milk with stirring speed of 400 rpm which was tested at 24 hours. The parameters tested were pH, Lactic Acid, Viscosity and Antioxidants. The results obtained in the form of a very significant increase in lactic acid in the Carrot variant with a Starter 3% and Broccoli 5% with a concentration of 0.8145%; 0.945% for Goat Milk Variant and UHT Milk for Carrot Variant with 3% starter. Based on the results obtained, where the addition of vegetables obtained viscosity (Cp) of 6.4745; 7.9359; 8.2459; 8,344; 14,374; 17,389 in UHT milk and 6,7033; 6,1984; 5,0345; 9,7324; 7,755; 9,0171 in Goat milk.